Academia, qui es-tu? - Vervoordt, Axel; Cousseau, Henry-Claude; de Bartiral, René; de Wolf, Eddi; Lietaer, Bernard; Païni, Dominique; Romanelli, Giandomenico; Derycke, Luc; Chapelle de l'Ecole nationale supérieure des Beaux-arts, Paris (Gent : MER. Paper Kunsthalle, 2008)
Academia: Qui es-tu, examines the dynamical process of artistic creation. The site of the Chapelle de l'Ecole des Beaux-Arts in Paris serves as the venue to examine the interplay between inherited academic knowledge accumulated over centuries, education, and the subsequent transformation and transmission of that knowledge into a novel artistic creation; for short the cross-fertilization between art and knowledge.
Catalog of an exhibition held at the Chapelle de l'École des beaux-arts de Paris from September 10 -- November 23, 2008.
boek